1992
DOI: 10.1073/pnas.89.11.5113
|View full text |Cite
|
Sign up to set email alerts
|

Pregnenolone biosynthesis in C6-2B glioma cell mitochondria: regulation by a mitochondrial diazepam binding inhibitor receptor.

Abstract: The C6-2B glioma cell line, rich in mitochondrial receptors that bind with high affinity to benzodiazepines, imidazopyridines, and isoquinolinecarboxamides (previously called peripheral-type benzodiazepine receptors), was investigated as a model to study the significance of the polypeptide diazepam binding inhibitor (DBI) and the putative DBI processing products on mitochondrial receptor-regulated steroidogenesis. DBI and its naturally occurring fragments have been found to be present in high concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(137 citation statements)
references
References 25 publications
0
137
0
Order By: Relevance
“…22(R)-hydroxycholesterol bypasses all signal-transduction pathways and has direct access to mitochondria in which it is a substrate for P450scc enzyme [25]. The results shown in Figure 4 show that pretreatment with GTE or EGCG followed by a 1-h recuperation period inhibited the responsiveness of Leydig cells to subsequent incubation with 22(R)-hydroxycholesterol by 38.4% and 49.2%, respectively.…”
Section: Effect Of Pretreatment With Gte or Egcg On Hcgor Lhrh-stimulmentioning
confidence: 57%
“…22(R)-hydroxycholesterol bypasses all signal-transduction pathways and has direct access to mitochondria in which it is a substrate for P450scc enzyme [25]. The results shown in Figure 4 show that pretreatment with GTE or EGCG followed by a 1-h recuperation period inhibited the responsiveness of Leydig cells to subsequent incubation with 22(R)-hydroxycholesterol by 38.4% and 49.2%, respectively.…”
Section: Effect Of Pretreatment With Gte or Egcg On Hcgor Lhrh-stimulmentioning
confidence: 57%
“…These cell types have been demonstrated previously to synthesize steroids (Hu et al, 1987;Papadopoulos et al, 1992), and this was verified for astrocytes with HPLC (data not shown). Expression of P450 scc was observed by immunoblot analysis of protein from isolated mitochondrial preparations (data not shown).…”
Section: Star Expression Can Be Induced In Cultured Glial Cellsmentioning
confidence: 86%
“…This approach is so far hampered by the lack of knowledge concerning the regulation of the biosynthetic pathways of neurosteroids. Ligands of the MBR have been shown to increase the synthesis of neurosteroids in cultured glioma cells (Papadopoulos et al, 1992) and in the brain Romeo et al, 1993;Bitran et al, 2000). The possibility to increase the synthesis of neuroactive steroids has stimulated recent efforts to develop new more selective and efficient MBR ligands.…”
Section: Discussionmentioning
confidence: 99%